Modelling of the 3R Motion at Non-Parallel Planes (Journal of Informatics and Mathematical Sciences, 2012)
We construct two similar planar mechanisms which have different and non-parallel planes. We build up a new connection between these mentioned mechanisms in this paper. How the motion of a mechanism is carried to another plane without making a difference in mechanism algorithm and some necessary mathematical relationships are found out. Therefore, a mechanism structure can be transported from one of the intersecting planes to another planes without changing its mechanism algorithm. This mechanism structure is as finger motion and the most important result is this.
Keywords: Motion; Synchronized; Mechanism